The in-vivo assessment of Turkish propolis and its nano form on testicular damage induced by cisplatin - Seven, Pinar Tatli; Seven, Ismail; Karakus, Selcan; Mutlu, Seda Iflazoglu; Kaya, Seyma Ozer; Arkali, Gozde; Kilislioglu, Ayben (Elsevier, 2021)
Objective: Chemotherapeutic drugs, such as cisplatin (CP), which are associated with oxidative stress and apoptosis, may adversely affect the reproductive system. This study tests whether administration of propolis and nano-propolis (NP) can alleviate oxidative stress and apoptosis in rats with testicular damage induced by CP. Methods: In this study, polymeric nanoparticles including propolis were synthesized with a green sonication method and characterized using Fourier transform-infrared spectroscopy, Brunauer-EmmettTeller, and wet scanning transmission electron microscopy techniques. In total, 56 rats were divided into the following seven groups: control, CP, propolis, NP-10, CP + propolis, CP + NP-10, and CP + NP-30. Propolis (100 mg/kg), NP-10 (10 mg/kg), and NP-30 (30 mg/kg) treatments were administered by gavage daily for 21 d, and CP (3 mg/kg) was administered intraperitoneally in a single dose. After the experiment, oxidative stress parameters, namely, malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GPx), and catalase (CAT), and apoptotic pathways including B cell leukemia/lymphoma-2 protein (Bcl-2) and Bcl-2-associated X protein (Bax) were measured in testicular tissues. Furthermore, sperm quality and weights of the testis, epididymis, right cauda epididymis, seminal vesicles and prostate were evaluated. Results: Propolis and NP (especially NP-30) were able to preserve oxidative balance (decreased MDA levels and increased GSH, CAT, and GPx activities) and activate apoptotic pathways (decreased Bax and increased Bcl-2) in the testes of CP-treated rats. Sperm motility in the control, CP, and CP + NP-30 groups were 60%, 48.75%, and 78%, respectively (P < 0.001). Especially, NP-30 application completely corrected the deterioration in sperm features induced by CP. Conclusion: The results show that propolis and NP treatments mitigated the side effects of CP on spermatogenic activity, antioxidant situation, and apoptosis in rats. (C) 2021 Shanghai Yueyang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine. Published by ELSEVIER B.V. All rights reserved.
Keywords: Cisplatin; Nano-propolis; Reproductive system; Testicular damage